PUBLIC SPHERE MEDIATIZATION - Аbysova Marya (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
The article is devoted to the analysis of the public sphere of modern society as a complex and dynamic phenomenon of so-cial and political interactions involved in the virtualization, mediatization and digitalization processes. The space of the digital public sphere, in contrast to the traditional public sphere one, is controlled by means of algorithms – hidden mechanisms integrated into many information platforms responsible for structuring of information on public platforms where people can discuss issues of concern. The ar-guments of techno-optimists and techno-pessimists regarding the effectiveness of digital activity and its risks in short-term, action-oriented practices and long-term perspectives are given. The search for consensus in the definition of digital activism makes the debate about its nature, harm and benefit to society of great current interest, encourages for the further study of the given problem.